On Asymptotic Pointwise Contractions in Modular Metric Spaces - Afrah A. N. Abdou (Abstract and Applied Analysis)
In this paper we study and prove some new fixed points theorems for pointwise and asymptotic pointwise contraction mappings in modular metric spaces.